RAINWATER HARVESTING AS AN ALTERNATIVE SOURCE OF DOMESTIC WATER IN LAMPUNG PROVINCE - INDONESIA - Gatot Eko Susilo; Tri Budi Prayogo (TATALOKA, 2019)
Urban areas in Indonesia will experience water crisis in the future due to the rapid population growth. Local water companies will face big problems to meet the water needs of these cities in the future, due to limited water resources and environmental degradation. Efforts to find new alternative water sources are important to undertake in order to ensure the availability of clean and fresh water in the future. This paper aims to investigate the effectiveness of rainwater harvesting facility and the potential benefits of rainwater harvesting applications in urban areas in Indonesia. The cities that are the object of research are Bandar Lampung, Pringsewu, and Metro City. These three cities are the fastest growing cities in Lampung Province. Simulation to find supporting capacity of RWH is applied for house type 45, which has an effective rooftop area of 30 m2. The maximum capacity of the tanks being tested is 1 m3 and 2 m3, and the number of occupants is 5 to 7 people. Research shows that RWH has great potential to meet domestic water demand in major cities in Indonesia. From some analysis and simulation of this research, it is known that the supporting capacity of RWH for domestic water supply in the cities studied is 40% to 50% on average. Research also shows that reservoir size 2 m3 is the most recommended dimension in RWH implementation in Lampung Province cities.